2009
DOI: 10.1007/s10620-008-0448-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Spectrum of Vulva Metastatic Crohn’s Disease

Abstract: Crohn's disease is a chronic granulomatous disorder that may involve any segment of the gastrointestinal tract. Extraintestinal manifestations of Crohn's disease such as erythema nodosum and pyoderma gangrenosum are well recognized and appreciated. However, metastatic Crohn's disease (MCD), defined as the same granulomatous inflammation seen in Crohn's disease but at a skin site distant to the gastrointestinal tract, is less well recognized. We report three cases of MCD involving the perianal and vulvar skin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 12 publications
(16 reference statements)
0
27
0
1
Order By: Relevance
“…[11][12][13] Metastatic CD has been defined as granulomatous inflammation of the skin that is not contiguous with the GI tract. [5][6][7][14][15][16][17] Although the literature documents both forms of vulvar CD, more than 90% of the published cases depict noncaseating granulomas in noncontiguous sites. 8,18 In our 20-year institutional review, we found a more varied clinical, epidemiological, and histopathological range of features, arguing for a broader definition of metastatic vulvar CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] Metastatic CD has been defined as granulomatous inflammation of the skin that is not contiguous with the GI tract. [5][6][7][14][15][16][17] Although the literature documents both forms of vulvar CD, more than 90% of the published cases depict noncaseating granulomas in noncontiguous sites. 8,18 In our 20-year institutional review, we found a more varied clinical, epidemiological, and histopathological range of features, arguing for a broader definition of metastatic vulvar CD.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly described histological finding in the literature is noncaseating granulomas, 8,11,[13][14][15]18,26,[32][33][34][36][37][38] which more than 90% of biopsies disclose. In our series, only 38% of patient biopsies had noncaseating granulomatous inflammation, a finding associated with a range of clinical signs, including ulcers, vulvar swelling, and exophytic lesions, consistent with what appears in prior reports.…”
Section: Discussionmentioning
confidence: 99%
“…Extra-intestinal cutaneous manifestations of Crohn's disease, like erythema nodosum and pyoderma gangrenosum, are well known. [2] Ulcerative vulvar Crohn's disease was first described by Park et al [3] It is very rare, and less than 60 such cases have been described. [4] Although the average age of presentation is 34 years, there have been reports in children as young as 8 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases have occurred in women who had inflammatory bowel disease or who were otherwise immunosuppressed. 3,4,6,8,9 Seven of the reported vulvar pyoderma gangrenosum cases were treated with steroids and one case was treated with cyclosporine. 3 Cyclosporine is a medication that inhibits both cellular and humoral immunity.…”
Section: Commentmentioning
confidence: 99%